2016
DOI: 10.1097/md.0000000000002453
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Invasive Breast Cancer Heterogeneity Using Whole-Tumor Magnetic Resonance Imaging Texture Analysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Ko et al reported that entropies derived from T 1 -weighted contrast-enhanced and T 2weighted imaging differed significantly among breast cancers with different differentiation degrees. 30 Since there were only three cases of well-differentiated gastric cancers in our cohort, more patients should be accumulated in our future work to make more reliable conclusions.…”
Section: Discussionmentioning
confidence: 90%
“…Ko et al reported that entropies derived from T 1 -weighted contrast-enhanced and T 2weighted imaging differed significantly among breast cancers with different differentiation degrees. 30 Since there were only three cases of well-differentiated gastric cancers in our cohort, more patients should be accumulated in our future work to make more reliable conclusions.…”
Section: Discussionmentioning
confidence: 90%
“…Wu et al 25 reported an association between peritumoral heterogeneity and a gene signature partially associated with immune cell recruitment and inflammation. Others have reported high lymphocytic infiltration to be associated with texture entropy features, 69 qualitative tumor enhancement profile and margin appearance in TN tumors, 70 and background parenchymal enhancement within 20 mm from the tumor. 71 Associations between intratumoral 72 and peritumoral 73 textural heterogeneity features with immune response at the molecular and morphometric scale have also been reported in the context of lung computed tomography.…”
Section: Discussionmentioning
confidence: 96%
“…Texture analysis was used to evaluate collagen heterogeneity in localized ROI’s through quantification of entropy, uniformity, and fractal dimension. Entropy is a measure of irregularity in the distribution of collagen within tissue and quantified using histogram analysis by the equation: , where P(V) represents the intensity occurrence probability and V represents the area fraction of collagen 21 . Uniformity is a measure of how close the image is to a uniform distribution and is quantified by the equation: .…”
Section: Methodsmentioning
confidence: 99%